Morbidity and measures of the diagnostic process in primary care for patients subsequently diagnosed with cancer. (30th November 2021) - Koo, Minjoung M; Swann, Ruth; McPhail, Sean; Abel, Gary A; Renzi, Cristina; Rubin, Greg P; Lyratzopoulos, Georgios
Abstract: Background: There is uncertainty regarding how pre-existing conditions (morbidities) may influence the primary care investigation and management of individuals subsequently diagnosed with cancer. Methods: We identified morbidities using information from both primary and secondary care records among 11, 716 patients included in the English National Cancer Diagnosis Audit (NCDA) 2014. We examined variation in 5 measures of the diagnostic process (the primary care interval, diagnostic interval, number of pre-referral consultations, use of primary care-led investigations, and referral type) by both primary care- and hospital records-derived measures of morbidity. Results: Morbidity prevalence recorded before cancer diagnosis was almost threefold greater using the primary care (75%) vs secondary care-derived measure (28%). After adjustment, there was limited variation in the primary care interval and the number of pre-referral consultations by either definition of morbidity. Patients with more severe morbidities were less likely to have had a primary care-led investigation before cancer diagnosis compared with those without any morbidity (adjusted odds ratio, OR [95% confidence interval]: 0.72 [0.60–0.86] for Charlson score 3+ vs 0; joint P < 0.001). Patients with multiple primary care-recorded conditions or a Charlson score of 3+ were more likely to have diagnostic intervals exceeding 60 days (aOR: 1.26 [1.10–1.45] and 1.19 [>1.00–1.41], respectively), and more likely to receive an emergency referral (aOR: 1.60 [1.26–2.02] and 1.61 [1.26–2.06], respectively). Conclusion: Among cancer cases with up to 2 morbidities, there was no evidence of differences in diagnostic processes and intervals in primary care but higher morbidity burden was associated with longer time to diagnosis and higher likelihood of emergency referral. Lay Summary: Individuals with pre-existing long-term conditions (morbidities) may have a different pathways leading to their cancer diagnosis compared with those without such conditions but detailed evidence is limited. We aimed to investigate how morbidities were associated with a range of measures of the diagnostic process in primary care. We examined morbidity in 2 ways, using information from a primary care audit and hospital records. We found that three-quarters of patients were living with 1 or more conditions according to primary care-based information, while the prevalence was almost threefold lower when estimated using hospital records. There was little difference in the time from first primary care appointment to specialist referral and the number of appointments before specialist referral by morbidity, particularly when comparing patients with 1 or 2 conditions vs those without. However, patients with multiple conditions or more serious diseases experienced lower likelihood of investigation, greater likelihood of being sent to the hospital as an emergency, and longer time to diagnosis. We did not find evidence of substantial differences in primary care-based diagnostic processes by morbidity. However, once an initial referral has been made, multiple or more severe conditions appear to influence the time taken to reach a diagnosis.